Book review: Katrine Marçal, Who Cooked Adam Smith's Dinner: A Story About Women and Economics. Issue 2 (August 2019) - Narayan, Swati
Katrine Marçal, Who Cooked Adam Smith's Dinner: A Story About Women and Economics . Translated by Saskia Vogel, London, UK: Portobello Books, 2015 (Reprint 2017), 320 pp. ISBN 978-1-84627-566-1.